Brasilianoids A–F, New Meroterpenoids From the Sponge-Associated Fungus Penicillium brasilianum - Zhang, Jianping; Yuan, Bochuan; Liu, Dong; Gao, Shuang; Proksch, Peter; Lin, Wenhan (Frontiers in Chemistry, 2018)
3,5-Dimethylorsellinic acid (DMOA) derived meroterpenoids comprise an unique class of natural products with diverse scaffolds and with a broad spectrum of bioactivities. Bioinformatics analysis of the gene clusters in association with the qRT-PCR detection of the amplification of two key genes led to speculate that the sponge associated fungus Penicillium brasilianum WZXY-m122-9 is a potential producer of meroterpenoids. Chromatographic separation of the EtOAc extract of this fungal strain on a large-scale fermentation resulted in the isolation of six new DMOA-related meroterpenoids with trivial names of brasilianoids A‒F (1-6), together with preaustinoid D and preaustinoid A2. The structures were determined by extensive analyses of spectroscopic data, including the X-ray diffraction and the ECD data for configurational assignment. Brasilianoids A and F showed an unprecedented skeleton with a -lactone in ring A, while brasilianoids B‒C featured a 7/6/6/5/5 pentacyclic ring system finding in nature for the first time. The biosynthetic relationship among the isolated compounds was postulated. Compound 1 significantly stimulated the expression of filaggrin and caspase-14 in HaCaT cells in dose-dependent manner, while compounds 2 and 3 showed moderate inhibition against NO production in LPS-induced RAW 264.7 macrophages.